Application of Lean Manufacturing System to Reduce Production Time: A Case Study of Khanom Jeen Fermented Flour Rice Noodles Factory - Jirasirilerd, Ganokgarn; Ponsri , Natawut (Thai Industrial Engineering Network Journal, 2023)
This article applied the lean manufacturing system with the objective of reducing the production time of khanom jeen fermented flour rice noodles. The problem analysis utilized the seven waste elimination tools and applied the flow process chart, including the ECRS principles, to solve the problem. Based on the study results, the lean manufacturing system application for problem solving could decrease the delay of work and eliminate unnecessary motion with layouts adjusting the machine. As a result, the process of khanom jeen fermented flour rice noodles decreased the production time from 360.88 minutes to 342.08 minutes, representing 5.21 percentages.